Proceedings of the Annual Symposium on Computer-Human Interaction in Play 2020
DOI: 10.1145/3410404.3414244
|View full text |Cite
|
Sign up to set email alerts
|

Disambiguating Preferences for Gamification Strategies to Motivate Pro-Environmental Behaviour

Abstract: Much topical gamification research has focused on the application of personality trait models and the development of player typologies. These models are often applied under the assumption that personality or gamification user type reside as a stable construct within the individual. However, the preference for gamification strategies as well as their motivational impact, may vary in different contexts and situations. Therefore, our study aimed to disambiguate the different levels of motivation (global, contextu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…Participants scored positive on both intrinsic and extrinsic motivation, and negative on amotivation. Compared to other studies [30,32], it is remarkable that participants in our study scored equally high on extrinsic levels of motivation as intrinsic levels of motivation.…”
Section: Rq2 Does Motivation For Self-management Of Health Mediate the Preference Towards Motivational Design Techniques?contrasting
confidence: 69%
See 3 more Smart Citations
“…Participants scored positive on both intrinsic and extrinsic motivation, and negative on amotivation. Compared to other studies [30,32], it is remarkable that participants in our study scored equally high on extrinsic levels of motivation as intrinsic levels of motivation.…”
Section: Rq2 Does Motivation For Self-management Of Health Mediate the Preference Towards Motivational Design Techniques?contrasting
confidence: 69%
“…These authors found that preferences for MDT indeed differ among older adults, but furthermore, preferences are associated with initial levels of intrinsic, extrinsic and amotivation. Recent studies in different fields have echoed similar findings [31][32][33][34][35]. These studies equally show initial levels of motivation towards behaviour that influence the preference for specific MDT.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…These results highlight the necessity to tailor gamification, considering both player types and learner initial motivationsomething that has been recently investigated in the field of pro-environmental behavior by Vanhoudt et al [19]. Finally, we provide design recommendations on the game elements to use in education according to these two factors.…”
mentioning
confidence: 55%